2011
DOI: 10.1016/j.ypmed.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

College student reactions to health warning labels: Sociodemographic and psychosocial factors related to perceived effectiveness of different approaches

Abstract: Objective To examine factors associated with perceiving different types of pictorial cigarette health warning labels as most effective in motivating smokers to quit or preventing smoking initiation among college students. Method We administered an online survey to 24,055 students attending six Southeast colleges in Fall, 2010. We obtained complete data for the current analyses from 2,600. Results Current smoking prevalence was 23.5%. The largest majority (78.6%) consistently rated gruesome images as most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…Third, labels with the greatest effects on discouragement from wanting to smoke generally included photographs of diseased body parts, suffering or dead people or children or babies, whereas labels with minimal effects generally included images consisting of art graphics, metaphors or depictions of unpleasant smoking experiences. These latter findings converge with evidence that labels with graphic depictions of disease have stronger effects on emotional reactions and smoking motivations than do images of human suffering or symbolic images 15 17…”
Section: Discussionsupporting
confidence: 69%
“…Third, labels with the greatest effects on discouragement from wanting to smoke generally included photographs of diseased body parts, suffering or dead people or children or babies, whereas labels with minimal effects generally included images consisting of art graphics, metaphors or depictions of unpleasant smoking experiences. These latter findings converge with evidence that labels with graphic depictions of disease have stronger effects on emotional reactions and smoking motivations than do images of human suffering or symbolic images 15 17…”
Section: Discussionsupporting
confidence: 69%
“…The overall response rate among eligible young adults was 19%, similar to other young adult internet-based smoking studies. 24 …”
Section: Setting and Samplementioning
confidence: 99%
“…In response to each of the pack images, participants answered a question assessing how much the pack motivated them to quit smoking using a 1-("Not at all") to 7-("A lot") response scale. 24 For bivariate analyses, we averaged participants' reported motivation to quit for the four pack images to assess associations with variables of interest (M = 4.82, SD = 1.83, Cronbach's α = 0.92). For multivariable analyses, we analyzed participants' responses to each item individually using methods to account for the within-participant correlated nature of the data (see statistical analysis description).…”
Section: Outcome Variablementioning
confidence: 99%
“…However, the research on cigarette warning labels shows that labels are effective in deterring cigarette smoking among college students (23)(24)(25). This research has also shown that the type of cigarette warning labels used (graphic images of disease, images of suffering with testimonials, or emotional tone) affects students differently depending on their smoking status (25).…”
Section: Introductionmentioning
confidence: 91%
“…College students are receptive to different antismoking messages depending on their smoking status (25,79). Accordingly, smoking status should be considered when antismoking messages for college-age adults are developed.…”
Section: Risk Communication Strategiesmentioning
confidence: 99%